(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
This article explores how artificial intelligence (AI) is reshaping the landscape of film and video production, with particular attention to gender and geographical inclusivity. By analyzing recent innovations across the entire production pipeline, from scriptwriting and directing to post-production and distribution, it highlights how AI tools reduce barriers of entry and redefine creative labor. A special focus is given to China’s role in advancing generative AI technologies, especially through open-source and low-cost platforms that make professional-grade video tools accessible to independent creators. The article also examines the gendered implications of these changes, considering how AI can support female filmmakers by easing time constraints, offering flexible workflows, and potentially mitigating some of the industry’s long-standing structural inequalities. While AI presents significant opportunities for democratizing access and amplifying diverse voices, the article also addresses key ethical and creative risks, such as algorithmic bias, homogenization of content, and labor displacement. Drawing on recent case studies and policy developments, the article argues that for AI to truly foster inclusion and innovation, it must be developed and adopted with human values at its core, ensuring that technology empowers rather than replaces creative agency.